Sustainability of Housing: The Conceptual Framework - Tai Martins, Adenipekun (Advanced Aspects of Engineering Research Vol. 5, 2021)
Housing is in fact more expensive product than many consumer goods. It is very productive because it is seen to account for more than 75% of household wealth. Yet, it sinks quickly into the sea of contradiction inflicted by imported knowledge against the local knowledge, techniques and traditions of users. Hence, it becomes very difficult for housing to meeting the needs of future users even if it strived to meet the requirements of the present users. This is the crux of this paper. The paper therefore reviews the elements of housing infrastructure and the challenges experienced in meeting future needs of users. It focuses on the sustainability of physical, cultural and productive functions of housing to draw its conclusion and recommendations.